Analisis Pengaruh Rasio Keuangan Dan EVA Terhadap Harga Saham Bank - Silalahi, Rizal (Business and Management Review, 2012)
Financial Ratio and Economic Value Added (EVA) have received a lot of recognition as a measure of prediction of share price.  While the measure has been widely used    for the purpose  of business in   all over the world, many research studies have appeared to examine variety of issues related to EVA in banking sector. An attempt has been made in this paper to  call  EVA-based analysis  for the Indonesian Banking Industry. A Sample of 10 public sector banks listed in Indonesia Stock Exchange has been selected using judgmental sampling. The financial data of these sample units for four years, 2008-2011, have been used for the analysis and comparison. Equity approach has been followed to compute EVA. Economic Value Added (EVA) is now being considered as an important management tool across the  banking  world for measuring and rewarding performance inside the  bank. Most of the  banks  measure performance with accounting profits which are often seriously measure of profitability.  EVA  is another measure of profitability. Unlike financial ratio such as ROA, ROE, NPM, DER,  EVA indicates the value to what extent created by management or agent for shareholders. This paper aims to analyze banks' performance  through  financial ratio and  EVA . For this purpose, EVA has been calculated taking certain assumptions as to the cost of equity and operational profit adjustments. A rank of regression coefficient between Share Price and different criteria indicates the decreasing rank from the highest to the  lowest under Return on Asset (ROA),  Debt to Equity (DER), Economic Value Added  (EVA)  and    Net Profit Margin  (NPM)  Dividend Payout Ratio (DPR), Return on Equity (ROE) and Debt to Asset Ratio (DAR).  ROA, DER, NPM, and EVA show a positive and significant explanatory power on Share Price in all ten samples. On the other hand, ROE, DPR, DAR show a negative explanatory power for Share Price in the banking sectors (t-value = negative; p-value = 0.05) demonstrates an insignificant relationship with Share Price in the banking sectors. According to the findings, EVA and some financial ratio are valuable performance measures for evaluating banking sectors. This study provides interesting and meaningful findings that EVA can be considered good performance measures throughout the banking sectors. In addition, the study found that  in banking sector traditional performance measures such as financial ratio ROA, DER, NPM  do not explain much of market adjusted return after considering EVA. Keywords: Financial Ratio, Economic Value Added and Share Price.